Hip Fracture Leads to Transitory Immune Imprint in Older Patients - Vallet, Héléne; Bayard, Charles; Lepetitcorps, Héléne; O'Hana, Jessica; Fastenackels, Soléne; Fali, Tinhinane; Cohen-Bittan, Judith; Khiami, Frédéric; Boddaert, Jacques; Sauce, Delphine (Frontiers in Immunology, 2020)
Background: Hip fracture (HF) is common in the geriatric population and is associated with a poor vital and functional prognosis which could be impacted by immunological changes. The objective here is to decipher immune changes occurring in the first days following HF and determine how phenotype, function and regulation of innate and adaptive compartments adapt during acute stress event. Methods: We included HF patients, aged over 75 years. For each patient, blood samples were taken at 5 different timepoints: four in the perioperative period (day 0 to hospital discharge) and one at long term (6-12 months). Phenotypical and functional analysis were performed longitudinally on fresh blood or cryopreserved PBMCs. Clinical data were prospectively collected. Results: 100 HF patients and 60 age-matched healthy controls were included. Innate compartment exhibits pro-inflammatory phenotypes (hyperleukocytosis, increase of CD14+ CD16+ proportion and CCR2 expression), maintaining its ability to produce pro-inflammatory cytokines. Adaptive compartment extends toward a transitory immunosuppressive profile (leucopenia) associated with an active T-cell proliferation. Furthermore, increases of LAG-3 and PD-1 and a decrease of 2-B4 expression are observed on T-cells, reinforcing their transitory suppressive status. Of note, these immune changes are transitory and sequential but may participate to a regulation loop necessary for homeostatic immune control at long term. Conclusion: HF is associated with several transitory immunological changes including pro-inflammatory phenotype in innate compartment and immunosuppressive profile in adaptive compartment. A comprehensive assessment of immune mechanisms implicated in the patient’s prognosis after HF could pave the way to develop new immune therapeutics strategies.